Testing and Improving a Continuous Requirements Risk Profiling Method - A Case Study on Agile Software Projects - Mustonen, Laura (My University, 2018)
As requirements play key role in the success of a software development project, identifying and mitigating requirements related risks becomes an important factor in improving software quality. Still, only few methods are offered for that purpose and little results of the feasibility of such methods in industry are reported. In this thesis, feasibility of one requirements risk management methodology was tested in agile software projects and an improved version of the method proposed. The tested method consists of identifying, prioritizing and resolving risks using predefined checklists, patterns and techniques. The objectives of the study were to gain knowledge do professionals working in agile software projects find the method feasible, are such methods found useful and how the method should be improved so that it could be taken into use in the case company. The study was conducted as an interpretive case study which covered several agile software projects from the case company. The primary data collection method for the study were semi-structured theme-centered interviews, in which the method was tested and evaluated by conducting a requirements risk analysis for each of the case projects. The key selection criteria for the interviewees was participation to requirements work and use of some agile software development methodology. The collected qualitative interview data was analyzed using thematic analysis. Based on the results of this study, it was observed that the tested method helped professionals to identify different type of requirements risks and to prioritize those on high level. The interviewed professionals found the tested method useful and feasible in the agile software projects they were currently working with. However, it was also observed that the resolution proposals provided by the method would still need further development. For researchers, the study provided empirical evidence on the feasibility of the method and several suggestions for further research. For professionals working in industry, the study provided one empirically validated method for managing requirements risk, and encouragement for collecting the existing requirements risk management knowledge and sharing it with corresponding methods and tools.
Keywords: Requirements engineering; Agile software development; Risk management; fi=Ohjelmistotekniikka (DI)|en=Software Engineering|; fi=Tietotekniikan koulutusohjelma (DI)|